Effect of fungicides on spore germination and myceilial growth of Colletotrichum capsici causing anthracnose of chilli - Pipliwal, Sunil Kumar; Godara, S L (Indian Journal of Plant Protection, 2022)
Anthracnose disease caused Colletotrichum capsici is a serious biotic stress affecting yield and quality of chilli fruits in India. Experiments were conducted to test selected fungicides for their inhibitory effect on spore germination and myceilial growth of C. capsici causing under in vitro conditions. It was found that fungicides viz., propiconazole, difenconazole, tebuconazole and hexaconazole were found most effective in inhibiting spore germination and myceilial growth of C. capsici.